Prevalence of ventilator-associated pneumonia through analysis of tracheobronchial secretions - Elenice Gomes Ferreira; André Kimura; Danielly Fernandes de Ramos; Pascoal Leite de Albuquerque; Mateus Dias Antunes; Daniel Vicentini de Oliveira (Rev Rene)
Objective: to verify the prevalence of pneumonia associated with mechanical ventilation through the collection and analysis of tracheobronchial secretions. Methods: an observational study with 13 male patients. The scale of Acute Physiology and Chronic Health Evaluation and the Clinical Pulmonary Infection Score were applied after 72 hours of orotracheal hospitalization. Results: an average score of 33 points was observed, that is, these patients presented on average a 75% chance of death. Staphylococcus aureus (23.07%) andKlebsiella pneumoniae (15.38%) were found as the most prevalent microorganisms.Conclusion: the prevalence of ventilator-associated pneumonia was 25% of the cases and the most prevalent microorganisms were Klebsiella pneumoniae and Staphylococcus aureus.